Pembangunan Alat Ukur Orintasi Seks Perlakuan Gay Dan Lesbian - Roslee Ahmad; Rezki Perdani Sawai; Muhammad Khairi Mahyuddin; Ahmad Najaa' Mokhtar; Salleh Amat; Mohd Isa Amat (Kementerian Pendidikan Malaysia, 2024)
Non-Indexed Publication